Verticalization of data sharing and the difficult path to eunnovation - Selçukhan Ünekbaş (Market and Competition Law Review)
Data sharing has been offered as a useful tool to open up impregnable markets to competition. EU law has a rich tradition in enabling business-to-business data sharing in a sector-specific (or vertical) fashion, which has formed the basis of the quest for an internal market where data flows freely. Two recent legislative instruments, the Digital Markets Act and the Data Act, contain industry- and actor-specific data sharing provisions. By unleashing troves of data hoarded by large incumbents, the Acts aspire to empower small and medium-sized enterprises, unlocking organic innovation. Notwithstanding the normative desirability of such a goal, it is unclear whether verticalized rules on data sharing can foster innovation by entrants and smaller undertakings. This Article legally and economically appraises the Acts to shed light on this issue. Read together, the data sharing provisions under the Digital Markets Act and the Data Act pursue the common aim of spurring disruptive (market creating) and complementary innovation. However, the Acts suffer from legal uncertainty and are liable to produce unintended economic consequences, such as diminishing the ability of complementors to satisfy consumers whilst simultaneously strengthening incumbent platform operators. The conclusions cast doubt on whether the vertical data sharing rules of the Acts can achieve their intended objectives, that is, ensuring the contestability of digital markets by promoting organic innovation by smaller scale firms.